The Implementation of Ice Breaking as A Learning Strategy to Improve the Concentration of Grade V Students at SDN Langaleso - Mau'izah; Latief, Juraid Abdul; Hasdin, Hasdin (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study examines the effectiveness of ice breaking as a learning strategy to improve the learning concentration of Grade V students at SD Negeri Langaleso. By employing a qualitative approach and a case study methodology, the research aims to gain an in-depth understanding of the phenomena occurring within the school environment. The research subjects are Grade V students of SDN Langaleso, with data collected through observation, interviews, and documentation techniques. The findings indicate that the implementation of ice breaking activities in the learning process can enhance student concentration. Ice breaking activities create a relaxed and enjoyable learning atmosphere, enabling students to concentrate better and become more receptive to the learning material. Based on the analysis, it can be concluded that ice breaking is an effective strategy for improving learning concentration, particularly among Grade V students at SD Negeri Langaleso. The study recommends applying similar strategies in other classes to comprehensively enhance the quality of learning.